The Effect of Online Consumer Reviews and Brand Image on Willingness to Buy at UC.N.CO Fashion Store with Brand Trust as a Mediation Variable (Case Study of UC.N.CO Store Customers in Berawa, Bali) - Beny Prasetyo; Gusti Ngurah Joko Adinegara; I Gusti Bagus Rai Utama; Tri Priyono Budi (Eastasouth Institute, 2026)
Willingness to Buy is a person's desire or intention to make a purchase after obtaining various information, either directly or indirectly. In the local fashion industry, such as UC.N.CO Berawa, purchasing decisions are not only influenced by product offerings, but also by other people's reviews and consumer perceptions of brand names/images. It is no longer new that online reviews are the main reference before purchasing, while a strong brand image can foster confidence that the product is worth choosing. These two aspects are related and form Brand Trust, which can encourage consumers to buy. This study was conducted with the aim of analyzing the influence of Online Consumer Reviews and Brand Image on Willingness to Buy, with Brand Trust as a mediating variable. The study was conducted using a quantitative approach with data collection using a Google Form questionnaire distributed to consumers who had visited or shopped at UC.N.CO Berawa. Seventy-seven respondents were collected using accidental sampling techniques. The data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method to detect the relationship between variables. The results of the study indicate that Online Consumer Reviews and Brand Image have a positive and significant effect on Brand Trust. However, neither has a significant direct effect on Willingness to Buy. Furthermore, Brand Trust plays an important role as a variable that connects these two factors with Willingness to Buy. These findings provide additional evidence that brand trust is a determining factor in consumer purchasing decisions, especially in the fashion industry.